Tips for Successful Transtibial Anterior Cruciate Ligament Reconstruction - Haro, Marc S.; Riff, Andy; Bach, Bernard R., Jr. (The Journal of Knee Surgery, 2014)
Anterior cruciate ligament (ACL) reconstruction is one of the most common procedures performed in orthopedics. While results from ACL reconstruction have been highly successful in restoring knee stability and allowing patients to return to sports, a debate continues as to which technique is best for restoring native anatomy and biomechanics. Some have proposed that a transtibial (TT) technique is not able to restore an ACL graft to the native femoral footprint and have advocated independent drilling of the femoral tunnel. We propose that with careful technique it is possible to reliably and reproducibly place the femoral tunnel in the anatomic femoral footprint using a TT technique with excellent results. We describe this surgical technique in detail and review the literature regarding the debate over TT drilling of the femoral tunnel and describe the senior author's (B.R.B.) experience using this technique.
Keywords: transtibial; anterior cruciate ligament; anatomic; femoral tunnel